Pollution legacy and land use influence peat chemistry in temperate lowland peatlands - Silverthorn, Teresa; Southon, Francesca; Chiverrell, Richard; Evans, Chris D.; Morrison, Ross; Andrews, L.; Holman, Ian P.; Baugh, L.; Bell, Chris; Boyle, J.; Baker, Francesca; Peacock, Mike (Wiley, 2026)
Peatlands slowly accumulate carbon and other elements over time, making them excellent archives of historical environmental conditions. A large proportion of low‐lying peat has been drained and converted to agricultural cropland or grassland use. Peatlands in some areas are also impacted by atmospheric deposition of metals from past industrial activities. We analyzed a suite of chemical elements in 13 peat cores from lowland peatlands across England with contrasting management histories, to assess the effects of these historic and recent human activities. The effects of peatland drainage were observed on organic matter content, which was significantly higher at semi‐natural sites compared to drained, grassland sites. We found peaks in metal concentrations (copper, lead, mercury and zinc) at bog sites in north‐east England, <50 km from a major hub of manufacturing during the industrial revolution. Arable and grassland sites had higher copper and phosphorous concentrations compared with semi‐natural sites, likely attributed to agricultural amendments such as fertilizers. Away from historic industrial sources, metal concentrations were generally below safe limits for soils. We demonstrate the impacts that humans have on lowland peat, providing insights to help inform rewetting and other restoration strategies.
Keywords: 37 Earth Sciences; 15 Life on Land; 3706 Geophysics; lowland peatlands; peatland drainage; peatland rewetting; pollution; metals; soil chemistry